Taxation : local government and real property taxation vol. 5 - Domondon, Abelardo T. (Manila : GIC Enterprises & Co., Inc., 2013)
This Volume V was updated bearing in mind the Note to coverage of the Law on Taxation for the 2013 bar Examinations.
I. Part I. Local Government Taxation -- II. Part II. Real Property Taxation.
Keywords: TAXATION -- PHILIPPINES; TAXATION; TAXATION -- PHILIPPINES -- EXAMINATIONS